Electrochemical Characterization Of Lithium Vanadium Oxide Anode With Agar Binder In Aqueous Rechargeable Lithium Ion Batteries - Lease, Jacqueline (Universiti Sains Malaysia, 2018)
The objective of this research is to study the effect of agar binder in lithium vanadium oxide (LiV3O8) anode on electrochemical and physical performance of the electrode. LiV3O8, graphene and agar binder were used to prepare LiV3O8 electrode in 8:1:1 ratio with different percentage of agar binder. The working electrode allowed to be characterized as a half-cell setting for the characterization. The structural analysis confirmed that the layered structure of LiV3O8 and graphene were formed. The binder was also successfully bind the matrix of active material and graphene together based on the morphology analysis. With the optimum scan rate (0.1 mV s-1) in cyclic voltammetry (CV), 8% agar electrode has the best performance. The high coefficient diffusion of lithium ions at 3.046 x 10-6 (anodic) and 1.315 x 10-6 cm2 s-1 (cathodic) for the peaks were also further determined by CV characterization. Low charge transfer resistances from impedance analysis in the anode half-cell showed the stability of the anode. The capacity of the anode fading slowly upon cycling. Best scan rate in charge/discharge has shown to obtain desirable initial specific charge and discharge capacities which are 51.20 mA h g-1 and 76.12 mA h g-1. A good cyclic performance with 84.1% capacity retention was obtained for 10 cycles at charge rate 2 C. Throughout the characterization, the anode will degrade at the initial cycles but return to stable after 25 cycles. LiV3O8 showed promising results when agar binder was added in this study.